2017
DOI: 10.1103/physrevd.95.043519
|View full text |Cite
|
Sign up to set email alerts
|

Core-halo mass relation of ultralight axion dark matter from merger history

Abstract: In the context of structure formation with ultralight axion dark matter, we offer an alternative explanation for the mass relation of solitonic cores and their host halos observed in numerical simulations. Our argument is based entirely on the mass gain that occurs during major mergers of binary cores and largely independent of the initial core-halo mass relation assigned to hosts that have just collapsed. We find a relation between the halo mass M h and corresponding core mass Mc, Mc ∝ M 2β−1 h , where (1 − β… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 71 publications
5
39
0
Order By: Relevance
“…We note that a power of η = 1/2 is derived analytically from self-similarity of the potential of the core and halo, which basically is the assumption: Mc/rc ∼ M/R h . On the other hand, η = 1/3 can be derived analytically from self-similarity of the energy of the core and halo: M It has also been suggested, in the literature, that Mc/M essentially follows from the mass loss in subsequent binary mergers (Du et al 2017). That work suggests Mc ∝ M 1.44(β−1) where β ≤ 1 is the descendant-to-originator mass-fraction.…”
Section: Soliton Core Mass Scalingmentioning
confidence: 99%
“…We note that a power of η = 1/2 is derived analytically from self-similarity of the potential of the core and halo, which basically is the assumption: Mc/rc ∼ M/R h . On the other hand, η = 1/3 can be derived analytically from self-similarity of the energy of the core and halo: M It has also been suggested, in the literature, that Mc/M essentially follows from the mass loss in subsequent binary mergers (Du et al 2017). That work suggests Mc ∝ M 1.44(β−1) where β ≤ 1 is the descendant-to-originator mass-fraction.…”
Section: Soliton Core Mass Scalingmentioning
confidence: 99%
“…the surrounding, CDM-like halo envelope, and that the size of the soliton and the halo mass are anti-correlated (Schive et al 2014a,b;Du et al 2017) rc = 1.6 kpc ma 10 −22 eV…”
Section: Ultra-light Axion (Ula) Subhaloesmentioning
confidence: 99%
“…The function f (ν) comes from the Sheth-Thormen model (Sheth and Tormen 1999) and it is given by f (ν (Marsh and Silk 2014;Bozek et al 2015) (in Marsh (2016b) a numerical fitting for this function was found). There are many other modifications of this HMF and alternative formulations that can be seen in Sheth and Tormen (1999), Bozek et al (2015), Du et al (2017b) and .…”
Section: Halo Density Profilementioning
confidence: 99%